Kathedralen - Grünenfelder, Josef, 1942-; De Langhe, J. E. (Joseph-Edgard), 1907-1998; Wolgensinger, Michael (Brussel : Artis-Historia, 1973)
Chartres, Bourges, Albi, Venetië, Florence, Rome, Chur, Lausanne, Sankt Gallen, Praag, Wenen, Salsburg, Konstanz, Spiers, Keulen, Doornik, Antwerpen, Santiago de Compostella, Sevilla, Durham, Lincoln